BDNF-Related Imbalance of Copine 6 and Synaptic Plasticity Markers Couples With Depression-Like Behavior and Immune Activation in CUMS Rats - Han, Yin-xiu; Tao, Chen; Gao, Xin-ran; Wang, Le-le; Jiang, Fu-hao; Wang, Chong; Fang, Ke; Chen, Xing-xing; Chen, Zheng; Ge, Jin-fang (Frontiers in Neuroscience, 2018)
Chronic stress is a contributing risk factor in the pathogenesis of depression. Although the mechanisms are multifaceted, the relationship can be ascribed partly to stress related alterations in immune activation and brain plasticity. Considering the increasing evidence regarding the role of Copine 6 in the regulation of synaptic plasticity, the aim of the present study is to investigate Copine 6 expression in the hippocampus and the PFC in a stress-induced depression rat model. The behavior of the rats was evaluated via the open field test (OFT), saccharin preference test, elevated plus-maze (EPM) test, tail-suspension test (TST), Morris water maze (MWM), and forced swimming test (FST). The plasma concentrations of C-reactive protein (CRP) and IL-6 were measured, and the protein expression of brain-derived neurotrophic factor (BDNF), Copine 6 and synaptic plasticity markers in the hippocampus and prefrontal cortex (PFC) were also detected. The results showed that chronic unpredictable mild stress (CUMS) induces depression-like behavior in rats, accompanied by increased plasma concentrations of CRP and IL-6. Moreover, the protein expression of BDNF, Copine 6, and synapsin I were decreased in both the hippocampus and PFC of CUMS rats, and the protein expression of synaptotagmin I was decreased in the hippocampus. Furthermore, Pearson’s test revealed a potential relationship between the depression-like behavior, the plasma CRP concentration, and the protein expression of BDNF, Copine 6, synapsin I or synaptotagmin I in the hippocampus or the PFC. Together with our previous results, the current findings suggest that apart from immune activation, the BDNF-related imbalance of Copine 6 expression in the brain might play a crucial role in stress-associated depression-like behaviors and synaptic plasticity changes.